Physicochemical, Phytochemical, and Stability Evaluation of a Polyherbal Syrup Formulated from Moringa oleifera, Phyllanthus emblica, and Curcumin longa - Parajuli, Guru Prasad; Paudel, Puskar; Bhandari, Arjun (Crimson Journal of Science and Technology, 2025)
Background: Herbal medicines are widely used due to their safety, accessibility, and minimal side effects compared to synthetic drugs. Moringa olefera, Phyllanthus emblica, and Curcuma longa are medicinal plants rich in bioactive compounds, including flavonoids, phenolic compounds, tannins, and antioxidants. Combining these herbs in a single formulation may produce synergistic therapeutic benefits suitable for use in respiratory and immune-related conditions. To formulate a polyherbal syrup using aqueous extracts of M. oleifera, P. emblica, and C. longa, and to evaluate its physiochemical properties, phytochemical composition, antioxidant activity, and stability under different temperature conditions.Methods: Dried leaves of M. oleifera and P. emblica, and C. longa were powdered and macerated in distilled water to obtain decoctions. Three formulations (S1, S2, and S3) were prepared using varying ratios of the decoctions and a fixed quantity of Chiuri honey as a natural preservative and thickening agent. Physicochemical parameters, including pH, specific gravity (pycnometer method), and viscosity (Ostwald viscometer), were measured. Qualitative phytochemical screening and DPPH antioxidant spot tests were conducted. Stability testing was carried out for seven days at cold (6 °C), hot (50 °C), and room-temperature conditions.Results: All extracts showed positive results for alkaloids, flavonoids, phenols, tannins, and antioxidant activity. The pH of formulations ranged from slightly alkaline (S1: 7.9) to mildly acidic (S2: 6.6; S3: 6.5). Specific gravity values were 1.18-1.19, and viscosity ranged between 2.32-2.71 Poise. Formulations remained stable under cold and room temperatures, while high-temperature exposure led to evaporation and reduced volume.Conclusion: The polyherbal syrup demonstrated desirable physicochemical characteristics, strong phytochemical presence, antioxidant potential, and good stability, indicating its suitability as a natural therapeutic preparation. Further quantitative phytochemical evaluation, antimicrobial assessment, and advanced instrumental analysis are recommended to validate and enhance its medicinal potential.